City and wind. Climate as an architectural instrument. - (:unkn) unknown (DOM Publ., 2013)
Spatial production is inevitably linked to climate issues. In the course of the last 15 years the debate on sustainable architecture and ecological urbanism has risen like a phoenix from the ashes. Architects and urban planners, as well as administrative bodies and developers, face a new responsibility in terms of the complexity of their conventional design and planning methods. Increasing awareness of climate issues in the design process has the potential once more to make architecture in the future more site-specific, giving it back its contextual relevancy. City and Wind - Climate as an Architectural Instrument is a call to see architecture not just as a means of protecting us against the climate, but also as a way of bringing us back to it.
Keywords: Bebauung; Stadt; Architektur; Städtebau; Klima; Stadtklima; Wind; Architekturgeschichte; Baugeschichte; Stadtplanung; Belüftung; Windenergie; Stadtgestaltung; Ökologisches Bauen; Beispielsammlung; Windschutz; Traditionelles Bauen; Klimawandel; Naturgewalt